From passive to viomatic or experience within: The evolution of education paradigms - Koutsopoulos, K. C. (International Journal of Educational Technology and Learning, 2026)
This paper, in dealing with the education paradigms, has the purpose of substantiating a new evolution scheme. The approach taken is based on two sources: On one hand, the examination of the presently accepted paradigm evolution scheme whose finding outlined a set of shortcomings that need to be overcome. On the other hand, the proposed paradigm evolution scheme suggests and substantiates the consideration of the following: first, competences constitutes a fundamental component in determining the educational process of a paradigm; second, educational entropy or the degree of disorder, uncertainty, or inefficiency impedes the effective paradigm development of information (e.g., construction/knowledge, application/skills and awareness /psychosocial factors); third, there is an educational triangle whose purpose is to provide students with the combined effect of the information development and its changes as the education paradigms shift; fourth, in today’s world, the sheer pace of change demands an experiential orientation, requiring a “viomatic”, or experience withing (accumulated), in order to achieve the goals of modern education; fifth, prioritizing experience means viewing the curriculum not as information mechanism to access educational contents, but as capacity to develop knowledge, skills, and awareness. Based on these, it is the unambiguous and categorical position of this paper that the scientific approach towards a new education paradigm evolution should be the increase of the information development and the degrease of the education system entropy.